The role of Biljana Plavšić in the early years of the Republika Srpska (1992–1998) - Skrzeszewska, Monika (Balcanica Posnaniensia. Acta et studia, 2017)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Biljana Plavšić was one of the leading politicians of the Republika Srpska in the 90s. During the war (1992–1995) she was called an Iron Lady because of her promotion of extreme nationalist views. This nickname previously belonged to the Prime Minister Margaret Thatcher because she was a strong politician. The question is whether Plavšić was an equally strong politician? After the war, she was the President of the Republika Srpska, but she was against her old political collaborators. In addition, as the only accused, Plavšić admitted her guilt during the Bosnian war in the International Criminal Tribunal of the former Yugoslavia. Her role, however, is usually neglected in the literature about war in Bosnia and Herzegovina, that is why, this article would like to discuss the Plavšić’s role.